Demonstration of two qubit entangling gates in a 2D ring resonator based coupler architecture - Anirban Bhattacharjee; Panya Jain; Jay Deshmukh; Srijita Das; Madhavi Chand; Meghan P. Patankar; R. Vijay (Scientific Reports)
Abstract We report entangling two-qubit experiments implemented in a novel ring resonator architecture in 2D planar geometry. The ring resonator acts as a multi-path coupler between qubits and can provide beyond nearest neighbour interactions. We demonstrate pairwise coupling between three fixed-frequency transmon qubits connected to the ring resonator with measured coupling strengths (4.70 MHz, 2.80 MHz, and 2.65 MHz) in good agreement with those predicted from finite-element simulations. We implement an all-microwave controlled phase (CPHASE) gate between a pair of qubits with a gate time of 196 ns and demonstrate a two-qubit Bell state with a measured state fidelity of $$F = 0.88$$ . Our results demonstrate the ability to entangle two qubits using the ring resonator and pave the way for creating highly connected multi-qubit networks in this architecture.